Effect Of Cognitive Behavioral Therapy On Reducing Anxiety, Stress And Depression In HIV-AIDS Patients : A Systematic Review - Riska Eka Fatma Hasibuan; Sri Yona; Anggri Noorana Zahra (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: HIV/AIDS remains a major public health issue, impacting patients' physical, social, and psychological well-being. Psychological effects like anxiety, stress, and depression are prevalent due to stigma, uncertain prognosis, and treatment complexity. Persistent stress weakens the immune system, accelerates disease progression, and reduces quality of life. Psychotherapy, such as Cognitive Behavioral Therapy (CBT), has been widely developed and proven effective in managing these issues. Objective: This study aims to examine the effect of CBT on reducing anxiety, stress, and depression in HIV/AIDS patients. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methods was used to select articles. Critical Appraisal Skills Programme was used for quality assessment. Discussion: This study reviewed ten articles on CBT's impact. Seven articles discussed CBT, two covered yoga therapy, and one explored mindfulness therapy. Results and Conclusions: CBT effectively reduces anxiety, stress, and depression in HIV/AIDS patients. Combining CBT with other therapies, such as Motivational Enhancement Therapy (MET), Medication Management Algorithm (MMA), and Enhanced Usual Depression Care (EUDC) plus the Healthy Options program, can provide additional benefits. CBT also improves patients' quality of life and has been shown to reduce HIV viral load.